A novel coordinative spatio-temporal operation strategy for EV battery swapping-charging system based on mobile battery energy storage - Zhijian Liu; Duanyu Li; Jing Dai; Pengcheng Li; Wenguo Yan (International Journal of Electrical Power & Energy Systems)
With the increasing penetration of electric vehicles (EVs) and renewable energy (RE), a battery supply system with flexibility and high cost-effectiveness is urgently needed. In this situation, mobile battery energy storage (MBES) is proposed as an intermediary for energy transfer, featuring spatio-temporal and power-energy controllability to assist the operation of the battery swapping-charging system (BCSS). Accordingly, a coordinated operation strategy for this spatio-temporal coupled joint system is proposed. This strategy considers the vehicle routing problem (VRP) of MBES, the battery swapping plan between MBES and the battery inventories of battery swapping stations (BSSs), and the charging management of batteries mounted on MBES. Given the NP-hard nature of the proposed MIP, an improved penalty feasible pump (IPFP) algorithm is designed to solve the model efficiently based on the highly efficient primal heuristics of feasible pump (FP). The spatio-temporal flexibility of the proposed model and the efficiency of the algorithm are verified through a case study. By employing an MBES working in bidirectional energy exchange mode of plug/swap (BEEM P/S) over 24 h, a total of 1089.71 kWh of RE can fully meet the random EV battery load of 1344 kWh, yielding a net benefit of $883.63.